The Effects of Learning Transfer on Clinical Performances Among Medical Staff: A Systematic Review of Randomized Controlled Trials - Tung, Yung-Chieh; Xu, Ying; Yang, Yu-pei; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Purpose. The purpose of this study was to evaluate the influence of learning transfer on the clinical performance of medical staff. Methods. We searched on PubMed, Embase, and the Cochrane Library for all associated studies without restrictions on language carried out from inception until December 31, 2021. Results. This systematic review screened out fourteen studies that met the inclusion criteria. Most of the studies showed that learning transfer contributed to the clinical performance of medical staff. Under the intervention of education, or when knowledge and skills have common basic principles, learning transfer will be more obvious than those who learn by themselves and those without simulation training. Conclusions. The findings of this review support an association between learning transfer and the clinical performance of medical staff. However, noted that due to the lack of relevant research and the large differences in the methods and indicators used in previous studies, we are restricted to conduct an effective meta-analysis. Further comprehensive trials will be needed to assess the impact of learning transfer on the clinical performance of medical staff.